2021
DOI: 10.1002/cche.10483
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on physicochemical properties of rice with germinated dark purple giant embryo rice and normal embryo rice

Abstract: Background and objectives As a cultivar developed by breeding, pigmented rice Keunnunjami has a dark purple pericarp and a giant embryo and has been found to possess strong antioxidant properties. The present study investigated the effect of 72‐hr germination on the physicochemical properties of Keunnunjami, in comparison with that of its parental pigmented normal embryo cultivar, Heukjinju, and ordinary normal brown rice. Findings Germination generally increased the amounts of reducing sugar, amino acids isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In another study, [ 1 ] reported that the germination of corn for 24 h led to a 79% increase in iron content and an 80% increase in zinc content. Furthermore, a study by [ 25 ] on germinated rice (normal brown, Heukjinju, and Keunnujami) indicated that calcium content increased and potassium content decreased. However, in the case of brown rice, all mineral substance values (calcium, magnesium, potassium, phosphorus) increased with germination.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, [ 1 ] reported that the germination of corn for 24 h led to a 79% increase in iron content and an 80% increase in zinc content. Furthermore, a study by [ 25 ] on germinated rice (normal brown, Heukjinju, and Keunnujami) indicated that calcium content increased and potassium content decreased. However, in the case of brown rice, all mineral substance values (calcium, magnesium, potassium, phosphorus) increased with germination.…”
Section: Resultsmentioning
confidence: 99%